A novel architecture to make anonymous blind signature-based e-coins more efficient and applicable. (8th May 2023) - Chen, Zhuo Qi
Blind signature-based (BSB) e-coins are powerful tools that provide anonymity and privacy protection in e-networks. We propose a novel architecture, comprising of a novel voucher-based blind signature scheme and database efficiency algorithm, for BSB e-coins. We find that our architecture reduces the data burden of the double spending detection database of any BSB e-coin system by at least 49.793598% and upwards to a negligible data burden when more ideal deposit patterns are facilitated, and increases BSB e-coin system scalability by causing operational costs per unit of time to increase much slower than growth in the size of the e-coin ecosystem in a growing BSB e-coin network. Our architecture if implemented can immediately reduce the cost of BSB e-coin networks in applications such as anonymised healthcare donor funding networks, anonymised voting, anonymous subscriptions, and ecommerce networks, among many others, and makes large-scale BSB e-coin systems much cheaper and more applicable.